Optimalisasi Kinerja: Stres Kerja, Kualitas Kehidupan Kerja dan Work-Life Balance dengan Mediasi Kepuasan Kerja pada Tenaga Kependidikan Unimus - Khusna Rakhmatika Putri; Edy Purwanto (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2026)
Background –In order to compete both domestically and globally, universities must enhance the caliber of their institutions and the effectiveness of their human resources due to the advancement of science and technology in the globalization period, especially in the context of Society 5.0. The success of academic services and the accomplishment of institutional objectives are strategically supported by educational staff. Aim – This study aims to analyze the effect of work stress, quality of Work-Life, and work-life balance on employee performance, with job satisfaction as a mediating variable. Design / methodology / approach – A total sample of 52 Unimus academic staff members provided quantitative data for the study. Likert scale-based questionnaires were employed in data collection methods. Structural Equation Model-Partial Least Squares (SEM-PLS) was the data analysis method used. Findings – Employee performance is not positively impacted by the three research variables—work stress, work-life balance, and quality of work-life. On the other hand, job satisfaction is positively correlated with work-life balance and work stress, which are negatively correlated with job satisfaction. In the meantime, employee performance is positively impacted by job satisfaction. The quality of work-life has a favorable impact on employee performance through the mediation of job satisfaction, while work stress and work-life balance do not have a good influence on employee performance. Conclusion - This study shows that an employee's performance in a work environment cannot always be determined by the variables commonly used in various studies, such as job stress, quality of work-life, and work-life balance. This is because not all individuals can be accurately measured using questionnaires related to the variables of job stress level, quality of work-life, work-life balance, job satisfaction, and performance. Research implication – This finding reinforces human resource management studies by emphasizing the importance of employee well-being and psychological conditions in improving performance. Limitations – This study focused only on Unimus academic staff, so the results cannot be generalized to all Unimus teaching staff.